2019
DOI: 10.1109/jbhi.2018.2819646
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Model to Predict Surgical Patients’ Lengths of Stay From an Electronic Patient Database

Abstract: Soaring healthcare costs and the growing demand for services require us to use healthcare resources more efficiently. Randomness in resource requirements makes the care delivery process less efficient. Our aim is to reduce the uncertainty in patients' resource requirements, and we achieve that objective by classifying patients into similar resource user groups. In this article, we develop a two-stage classification model to classify patients into lower variability resource user groups. There are various statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…If there is low likelihood, we predict LOS, if there is high likelihood we acknowledge we cannot do any better given the information we have. Kumar et al 27 developed a two-stage model that first predicted LOS before admission and then utilized predictors 5 days after admission. The predictors after admission improved the predictive accuracy of prolonged LOS.…”
Section: Discussionmentioning
confidence: 99%
“…If there is low likelihood, we predict LOS, if there is high likelihood we acknowledge we cannot do any better given the information we have. Kumar et al 27 developed a two-stage model that first predicted LOS before admission and then utilized predictors 5 days after admission. The predictors after admission improved the predictive accuracy of prolonged LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Steele and Thompson [63] developed a KNN-based pLOS prediction model for general patients and achieved an AUROC of 0.847. KNN was included as the base model in our study because it has shown superior performance in pLOS prediction in existing studies [63,64]. Given that its learning mechanism is different from the learning mechanisms of the 2 other base models (SVM and RF), KNN was expected to improve the prediction performance of the stacking model in dealing with data sets with various characteristics [37,59].…”
Section: Principal Findingsmentioning
confidence: 99%
“…We develop a strategy to keep a comparable level of uncertainty in the MIP model. Kumar and Anjomshoa [10] found that classification and regression tree (CART) analysis is useful for classifying patients into lower variability LoS groups. We applied CART analysis on the ICU LoS data from the partner hospital, and we classified patients into short-stay (SS), medium-stay (MS), and long-stay (LS) groups.…”
Section: Fundamental Concepts and Our Approachmentioning
confidence: 99%